Involvement of microRNA-34a in Age-Related Susceptibility to Oxidative Stress in ARPE-19 Cells by Targeting the Silent Mating Type Information Regulation 2 Homolog 1/p66shc Pathway: Implications for Age-Related Macular Degeneration - Tong, Nianting; Jin, Rong; Zhou, Zhanyu; Wu, Xingwei (Frontiers in Aging Neuroscience, 2019)
The aging retinal pigment epithelium and oxidative stress, mediated by reactive oxygen species accumulation, have been implicated in the mechanisms of age-related macular degeneration (AMD). The expression level of the adapter protein p66shc, a key protein that regulates cellular oxidative stress, is relatively low under normal conditions because of the effects of silent mating type information regulation 2 homolog 1 (SIRT1) on the binding of fully deacetylated histone H3’ to the p66shc promoter region, thus inhibiting p66shc transcription and expression. The equilibrium between SIRT1 and p66shc is disrupted in the presence of various stresses, including AMD. As a major target gene, SIRT1 is regulated by microRNA-34a (miR-34a), and overexpression of miR-34a results in significant inhibition of post-transcriptional expression of SIRT1. Furthermore, our recent studies demonstrated that miR-34a is significantly upregulated, accompanied by reduced tolerance to oxidative stress in hydrogen peroxide-induced prematurely senescent ARPE-19 cells. Moreover, the expression of SIRT1 is decreased, whereas that of p66shc is increased in these cells. Accordingly, miR-34a may play a key role in age-related susceptibility to oxidative stress in ARPE-19 cells by targeting the SIRT1/p66shc pathway, leading to AMD. In this review, we discuss the functions of miR-34a in modulating the SIRT1/p66shc pathway in age-related conditions, including AMD.